Implikasi KHK 1983 terhadap Kasus Pernikahan Campur dalam Beberapa Pandangan Dokumen Gereja Katolik - Skolastika Dinda Ayu Maharani; Bernadus Tito Pranoto (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This study explores the implications of the 1983 Code of Canon Law (CIC) on mixed marriages within the Catholic Church, focusing on its legal, pastoral, and social dimensions in the context of religious pluralism. Mixed marriages, involving a Catholic an a non-Catholic partner, pose unique spiritual and legal challenges due to differing faith backgrounds, the research aims to analyze how the CIC, alongsid Church documents such as Muto Proprio Matrimonia Mixta, Familiaris Consortio, and Amoris Laetitia, addresses these challenges while upholding the sacramental nature of marriage. A qualitative descretive method was employed, utilizing critical textual analysis of relevant literature, including books, journals, and Church documents, the findings highlight that Canons 1124-1126 og the CIC provide a robust legal framework requiring episcopal dispensation, commitment to Catholic faith preservation, and respect for the non-Catholic partner’s beliefs. these Canons balance the protection of Catholic identity with openness to interfainth dialogue. Additionally, Church documents emphasize pastoral accompaniment, compassion, and doalogue to foster family unity and fainth education for children. The study concludes that the CIC, enriched by pastoral approaches in the referenced documents, offers a framework that not only regulates mixed marriages but also transforms them into opportunities for spiritual growth and interreligious harmony, particularly in diverse societies like Indonesia. This integrated approach ensures the mixed mariages can be a source of blessing rather than conflict, promoting stability ant mutual respect in families.